(untitled) (Research, Society and Development, 2023)
The performance of the health psychologist within the hospital is focused on the suffering caused by the patient´s illness and the involvement of their family members, helping in the adaptive elaboration of the illness process. The hospital environment needs, in most cases, brief interventions, directives and focused on problem solving. Cognitive Behavioral Therapy (CBT) adapts well to the hospital, as it has a collaborative character, focused on current goals and problems, as well as being brief and structured. Adding to that, surgical procedures correspond to a common practice within the hospital institution. In terms of amputation surgery, it is the removal of a complete or a part of an organ, usually from one body end. Upon receiving the news that there is a need to perform the amputation, the feeling of loss and mourning is awakened in the individual. Depressive symptoms such as sadness, grief, crying episodes, social isolation, sleeping difficulty, appetite loss, among others, are frequent in patients undergoing amputation. The present study aims to identify the effectiveness of Cognitive Behavioral Therapy with hospitalized patients in the process of amputation, through a literature review. The aim of this article is to contribute to discussions on the topic of amputation and the applicability of CBT in this context.